2007
DOI: 10.1128/jb.01235-07
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Glucose Transport Causes Preferential Utilization of Aromatic Compounds in Pseudomonas putida CSV86

Abstract: Pseudomonas putida CSV86 utilizes aromatic compounds in preference to glucose and coutilizes aromatics and organic acids. Protein analysis of cells grown on different carbon sources, either alone or in combination, revealed that a 43-kDa periplasmic-space protein was induced by glucose and repressed by aromatics and succinate. Two-dimensional gel electrophoresis and liquid chromatography-tandem mass spectrometry analysis identified this protein as closely resembling the sugar ABC transporter of Pseudomonas put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…P. putida CSV86 preferentially utilizes aromatics or organic acids over glucose and co-metabolizes aromatics and organic acids . Previously, we have demonstrated that glucose induces glucose-6-phosphate dehydrogenase (Zwf), an intracellular glucose-metabolizing enzyme ) and a 43 kDa glucosebinding periplasmic space protein (Basu et al, 2007). Both Zwf and the 43 kDa protein are repressed by aromatics as well as by organic acids Basu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…P. putida CSV86 preferentially utilizes aromatics or organic acids over glucose and co-metabolizes aromatics and organic acids . Previously, we have demonstrated that glucose induces glucose-6-phosphate dehydrogenase (Zwf), an intracellular glucose-metabolizing enzyme ) and a 43 kDa glucosebinding periplasmic space protein (Basu et al, 2007). Both Zwf and the 43 kDa protein are repressed by aromatics as well as by organic acids Basu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Outer-membrane proteins were resolved by SDS-PAGE (10 %) as described by Laemmli (1970). Outer-membrane protein fractions were also subjected to 2D gel electrophoresis (Basu et al, 2007;Joshi et al, 2004;O'Farrell, 1975) followed by LC-MS/MS analysis (ESI-TRAP, trypsin digest; peptide mass tolerance±2 Da; fragment mass tolerance, 0.8 Da) as described by Basu et al (2007). The data were analysed by using the Mascot protein identification system (Matrix Science) with the database from The Institute of Genomic Research (TIGR; http://www.jcvi.org/).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In E. coli, the cAMP receptor protein Crp is involved in CCR of PAA degradation (Ferrández et al, 2000;Kimata et al, 1997;Notley-McRobb et al, 1997). However, the level of cAMP in P. putida remains constant regardless of the carbon source and cAMP is unlikely to be involved in CCR in this species (Basu et al, 2007;Siegel et al, 1977). CCR of PAA metabolism appears to be unaffected by organic acids, such as pyruvate or succinate (Kim et al, 2007), suggesting that CCR is generated by glucose intermediates (Fig.…”
mentioning
confidence: 99%